Obrazy Holocaustu w etiudach filmowych PWSFTviT w Łodzi - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
In Serach of the Form. Images of the Holocaust in student films of the Polish National Film School The article In Search of the Form is a contribution to the research on school films about Holocaust. The author analyzed over 20 short films produced in the National Film School in Lodz in 1948–2010. In great part these films reflect the general trend from the professional cinema of the same period. However young filmmakers appear to be more daring as far form of the films is concerned. Their films are aesthetically original, ofthe refer to genre cinema and combine different genres.